2020
DOI: 10.1007/s12630-020-01828-9
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative risk factors in patients with idiopathic pulmonary fibrosis: a historical cohort study

Abstract: Purpose Perioperative complications of patients with idiopathic pulmonary fibrosis (IPF) are not well described. The aim of this study was to identify risk factors associated with adverse postoperative outcomes in IPF patients. Methods We performed a single-centre historical cohort study of adult patients with IPF who underwent surgery between 2008 and 2018. We analyzed the prognostic utility of select perioperative factors for postoperative acute exacerbation of IPF (AE-IPF), acute respiratory worsening (ARW)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…62 Further supporting this observation, McDowell et al found an 5% incidence of AE-ILD in IPF populations with no significant difference between non-thoracic and thoracic study cohorts [N = 4 (thoracic) vs 6 (non-thoracic) RR: 1.16 (CI: 0.34 to 0.99 Q = 4.0). 22 Similarly, Takao et al found an incidence of 6.3% and mortality rate of 80% of AE-ILD in a cohort of all-ILD patients after non-pulmonary surgery. 37 …”
Section: Postoperative Management: a Focus On Avoidance Of Pulmonary ...mentioning
confidence: 87%
See 3 more Smart Citations
“…62 Further supporting this observation, McDowell et al found an 5% incidence of AE-ILD in IPF populations with no significant difference between non-thoracic and thoracic study cohorts [N = 4 (thoracic) vs 6 (non-thoracic) RR: 1.16 (CI: 0.34 to 0.99 Q = 4.0). 22 Similarly, Takao et al found an incidence of 6.3% and mortality rate of 80% of AE-ILD in a cohort of all-ILD patients after non-pulmonary surgery. 37 …”
Section: Postoperative Management: a Focus On Avoidance Of Pulmonary ...mentioning
confidence: 87%
“… 4 Another study demonstrated a correlation between preoperative home oxygen use and postoperative ARW in IPF patients, providing an easy identifier of higher-risk IPF patients (Relative Risk 2.70; 95% CI: 1.50, 4.86, P < 0.001). 22 Furthermore, IPF patients with <80% FVC on preoperative pulmonary function testing have been found to have increased cardiopulmonary complications and worse long-term survival after lung resection. 23 , 24 …”
Section: Preoperative Risk Assessment and Optimization Of Patients Wi...mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, cardiovascular conditions may include those such as unstable angina, congestive heart failure, previous stroke, or myocardial infarction within the last 3 months [9]. Patients with respiratory-related conditions such as chronic obstructive pulmonary disease or pulmonary fibrosis requiring oxygen supplementation may also be at higher perioperative risk [10]. Other conditions include history of poor wound healing due to poorly controlled diabetes or morbid obesity, resulting in a high anaesthetic risk.…”
Section: Introductionmentioning
confidence: 99%